Философия культуры - Черванева, Зинаида Александровна (НТУ "ХПИ", 2012)
Рассматриваются философские проблемы культуры, ее понимание, проявление и осмысление. Прослеживается путь культуры на разных этапах исторического развития; аксиологический и деятельностный, индивидуальный и групповой подходы осмысления культуры; семиотическая интерпретация ее; анализируются формы культуры — элитарная и массовая; обосновывается значимость философии культуры для жизнедеятельности общества и человека.

The philosophical problems of culture, its understanding, display and comprehension, are examined. The way of culture is traced on the different stages of historical development; axiological and activity, individual and group approaches of comprehension of culture; semiotics interpretation it; the forms of culture are analysed — elite and mass; meaning fulness of philosophy of culture is grounded for the vital functions of society and man.
Philosophy of culture
Keywords: история культуры; осмысление; ценности духовные; цивилизация; подход аксиологический; подход деятельностный; гуманизация